L’Éloge de la laideur dans la littérature antipétrarquiste - Jean-Pierre Cavaillé (L'Atelier du CRH, 2013)
On the basis of the analysis of an academic discourse from the philosopher Antonio Rocco in paradoxical praise of ugliness (1630), we distinguish several ways of dealing with ugliness within the Italian literature of the sixteenth and seventeenth centuries, which maintain a relationship of opposition or perversion with the Platonic model of Petrarchism: Marinist poets praise the defective beauty (the beautiful old woman, beautiful woman lame, etc.); Tasso’s theme of the sincere and conscious love of an ugly woman; and the burlesque and misogynic eulogium of the ugly woman (Lorenzo il Magnifico, Berni, etc.). In all these cases, the target is the ugliness of the woman's body. In a very eloquent way the Silenian pattern, often applied to the ugliness of men (an ugly body covering a beautiful soul), is unimaginable for women. We can also observe that the depreciation of the female body is generally in favor of the young male body in the framework of a discrete or clamorous valorization of sodomy. Thus, this literature which overcomes the prejudices of religious morality, does not lead in any way to the recognition of any gender equality.